2008
DOI: 10.1084/jem.20080406
|View full text |Cite
|
Sign up to set email alerts
|

VE-PTP maintains the endothelial barrier via plakoglobin and becomes dissociated from VE-cadherin by leukocytes and by VEGF

Abstract: We have shown recently that vascular endothelial protein tyrosine phosphatase (VE-PTP), an endothelial-specific membrane protein, associates with vascular endothelial (VE)–cadherin and enhances VE-cadherin function in transfected cells (Nawroth, R., G. Poell, A. Ranft, U. Samulowitz, G. Fachinger, M. Golding, D.T. Shima, U. Deutsch, and D. Vestweber. 2002. EMBO J. 21:4885–4895). We show that VE-PTP is indeed required for endothelial cell contact integrity, because down-regulation of its expression enhanced end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
200
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(207 citation statements)
references
References 64 publications
(64 reference statements)
5
200
2
Order By: Relevance
“…We found that the VEPTP promoter harbored 4 HREs, of which HRE2 showed the greatest HIF2α-dependent transctivation and was critical for VEPTP mRNA transcription. VE-PTP, an EC-specific transmembrane protein, forms a complex with VE-cadherin at AJs and is believed to mediate the assembly of AJs by VE-cadherin dephosphorylation (24). SRC kinase-dependent VE-cadherin phosphorylation (21) and VE-PTP-mediated dephosphorylation of VE-cadherin are important countervailing regulators of the remodeling and plasticity of AJs (31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the VEPTP promoter harbored 4 HREs, of which HRE2 showed the greatest HIF2α-dependent transctivation and was critical for VEPTP mRNA transcription. VE-PTP, an EC-specific transmembrane protein, forms a complex with VE-cadherin at AJs and is believed to mediate the assembly of AJs by VE-cadherin dephosphorylation (24). SRC kinase-dependent VE-cadherin phosphorylation (21) and VE-PTP-mediated dephosphorylation of VE-cadherin are important countervailing regulators of the remodeling and plasticity of AJs (31).…”
Section: Discussionmentioning
confidence: 99%
“…HIF2α-induced VE-PTP expression mediates AJ integrity through a reduction of VE-cadherin endocytosis. VE-PTP, through its interaction with VE-cadherin, regulates dephosphorylation of VE-cadherin (24), which is important in regulating VE-cadherin endocytosis-mediated internalization and hence determines the integrity of AJs (21,22). We therefore determined whether VE-PTP regulated VE-cadherin stability at AJs by modulating VE-cadherin internalization through an endocytotic mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, binding of certain leucocytes to endothelium dissociated the VE-PTP from VE-cadherin. 27 Another example is the transduction of mechanical stimulation into intracellular signals requiring VEGFR2, VE-cadherin, and PECAM-1. 28 Furthermore, VE-cadherin comprises a single membrane-spanning domain followed by a short carboxyterminal cytoplasmic domain that connects many regulatory molecules, including p120 ctn , β-, and γ-catenin.…”
Section: Short Overview Of the Ve-cadherin/ Catenin Complexmentioning
confidence: 99%
“…In the BM, G-CSF-induced upregulation of sinusoidal endothelial CD26 (dipeptidyl peptidase 4) has been indicated to be important for HSPC transendothelial migration and mobilization via cleavage of full length neuropeptide Y (NPY) to NPY3-36 [79]. The in vivo effects of G-CSF on EC are also influenced by the involvement of infiltrated neutrophils and their secreted proangiogenic cytokines such as vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF), which leads to neovascularisation [80,81] and dissociation of tight junction element vascular endothelial cadherin (VE-cad) [82,83]. However, it must be noted that G-CSF treatment does not lead to measurable vascular leakage as determined by Evans Blue perfusion [84].…”
Section: Endothelial Cells (Ecs)mentioning
confidence: 99%